ENDEMIC PLANTS OF MT. RINJANI: AN OUTLOOK TO THE CONSERVATION STRATEGY - Wita Wardani; Arief Hidayat; E F Tihurua; A Kartonegoro; L D Sulistyaningsih; E S Kuncari; E B Walujo (Floribunda, 2012)
Mount Rinjani, lies in the island of Lombok, is believed as the major source of plant diversity in the island today. This is caused primarily by the rapid land conversion on the less steep plains for agricultural industries. Although in sum of less than 50% of the estimated native plant species, the endemic inhabit the mountain area is of important in conservation since very limited information known to these species. At the same time, the habitat is threaten by tourism activities, mainly on the tracks lead to the caldera. There is an urgent need to esta-blish a working conservation strategy to ensure the sustainability of them. In this paper, the occurrence of endemic species based on herbarium records and literatures with the proposed conservation strategy is discussed